2022
DOI: 10.1111/1752-1688.13036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restoration on Plant Greenness and Water Use in Relation to Drought in the Riparian Corridor of the Colorado River Delta

Abstract: The unrestored delta riparian corridor continues to decline in EVI2 and ET but restoration has positively impacted habitats and contributed to the understanding of the continuing efforts of Minute 323.ABSTRACT: Revitalization of the Colorado River delta riparian corridor and increasing riparian plant greenness and water use may be accomplished by added water and restoration efforts to offset declines measured since 2000 by Landsat. We use the two-band Enhanced Vegetation Index (EVI2; a proxy for greenness) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Zamora-Arroyo et al ( 2001) determined that the minimum discharge necessary for the recruitment of willowcottonwood forests along the lower Colorado River was a modest flow of 3 Â 10 9 m 3 over a 3-month period that coincides with seed release timing (i.e., February-April). Like our findings, their results have clear implications for the management of flow releases from upstream dams to support native riparian forests but within dryland riparian systems such as the Santa Clara River and lower Colorado River, competing water uses for agricultural and municipal purposes is intense, making it difficult to balance human needs and conservation goals (Nagler et al, 2021;Nagler et al, 2022;Stromberg et al, 1996).…”
Section: Inflow Thresholds and Plant Health Resiliency To Projected C...supporting
confidence: 63%
“…Zamora-Arroyo et al ( 2001) determined that the minimum discharge necessary for the recruitment of willowcottonwood forests along the lower Colorado River was a modest flow of 3 Â 10 9 m 3 over a 3-month period that coincides with seed release timing (i.e., February-April). Like our findings, their results have clear implications for the management of flow releases from upstream dams to support native riparian forests but within dryland riparian systems such as the Santa Clara River and lower Colorado River, competing water uses for agricultural and municipal purposes is intense, making it difficult to balance human needs and conservation goals (Nagler et al, 2021;Nagler et al, 2022;Stromberg et al, 1996).…”
Section: Inflow Thresholds and Plant Health Resiliency To Projected C...supporting
confidence: 63%
“…The monitoring of riparian corridors at Landsat spatial scales of 30 m resolution, or finer, is imperative to comprehend the multifaceted impacts of climate variability [1-3], species invasions, habitat fragmentation, and acute disturbances such as wildfires and flooding. This is particularly critical in the arid and semi-arid regions of northwestern Mexico and the southwestern United States, where riparian vegetation is declining due to both anthropogenic pressures and natural stressors, such as increased temperatures and water scarcity [4]. These changes not only threaten biodiversity and ecosystem services but also have economic implications, affecting local economies that benefit from green spaces and recreational activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrological conditions in the study area are demonstrated by the disparity between surface flows and plant water use, creating a niche for predominantly phreatophytic plants which draw water from the aquifer [14]. These species are primarily riparian trees in the narrow Reach 4, where more than a dozen restoration sites are monitored [4,12,24,25], but in Reach 5 where the Delta truly begins to form and in Reach 7 where the river further meanders and spreads, the predominant species are no longer native riparian trees but rather shrubs such as Tamarix spp., with high fractions of low vegetation cover including saltgrass (Distichlis spicata) [24,25]. Minute 323 provided the framework for the restoration site infrastructure, the physical infrastructure for delivering water through weirs at four locations to deliver water (e.g., 2021-2022) into Reach 4, and the monitoring of riparian health outcomes compared with the unrestored riparian corridor [23].…”
Section: Introductionmentioning
confidence: 99%
“…2022) and wetlands health (Nagler et al. 2022)). In still other cases, this new Featured Collection addressed issues not explored in the original articles.…”
mentioning
confidence: 99%
“…Some articles in this Featured Collection revisited original analysis of the SSD (e.g., the role and implications of tree-ring research, impacts of drought on water-based recreation). Others explore earlier topics in greater detail (e.g., effects on fish species (Bruckerhoff et al 2022) and wetlands health (Nagler et al 2022)). In still other cases, this new Featured Collection addressed issues not explored in the original articles.…”
mentioning
confidence: 99%